Behavior of garlic cultivars in different planting times - Souza, Rovilson José de; Casali, Vicente Wagner Dias (Pesquisa Agropecuaria Brasileira, 2014)
A field trial was carried out at the Rio Paranaiba Experimental Station, of Minas Gerais State, Brazil (19°8 south and 1,150 m above sea level) on dark-red latosol. Production of three garlic cultivars Juréia, Amarante and Dourados at seven planting times (November 22, December 22, 1977 and January 23, February 22, March 22, April 22 and May 22, 1978) were compared. Planting times which promoted the highest yields varied with cultivars Juréia yielded the most from Feb. 22 to Apr. 22, Amarante from Jan. 23 to May 22 and Dourados at Feb. 22. Juréia and Dourados were the highest yielding cultivars and Amarante the lowest one. Planting times as early as November and December and as late as May caused a significant yield reduction.
Keywords: Allium sativum L.; white rot; seed garlic; medium bulbs; small bulbs